WHY GO TO SCHOOL IN PRISON? REFLECTIONS ON THE SIGNS ATTRIBUTABLE BY PRIVATE STUDENTS OF FREEDOM TO EDUCATION - Poennia Gadelha Soares, Carla; Vicente Viana, Tania (LINKSCIENCEPLACE, 2026)
The purpose of this paper is to discuss about the meanings that incarcerated students attribute to formal education. Sousa (2000, 2004), Goffman (2013), Figueiredo (2005, 2012) and Freire (2012, 2014) proposed a theoretical framework to this study. The results revealed that the educational actions inside the prisons, besides emphasizing the pragmatic contents, also exercise an edifying influence upon the captive’s life, creating such conditions that he/she can be able to understand and accept himself/herself as a social individual, being motivated to build a new life project.